Profitability of the Central Cooperative Banks in Punjab - A Decomposition Analysis - Singh, Balwinder (Indian Journal of Finance, 2011)
The cooperative banking system has witnessed a sea change since the initiation of the financial sector reforms in India from 1991-92. There has been a comprehensive change as regard to the profitability position of the central cooperative banks in Punjab. Two different years i.e., 1991-92 and 2008-09 have been studied with the help of a framework of Return on Equity (ROE) model. Both the conceptual and pragmatic approaches have been worked upon. The sample central cooperative banks with high business volume and those with low business volume have been tested separately. It could be concluded that as far as the profitability performance is concerned, the central cooperative banks of Punjab, have responded well. The miscellaneous income, in comparison to the total income, has been in low profile in these banks. The switching over to high yield non- farm sector advances has helped to register a positive trend in financial margins in almost all the banks. Although the implementation of prudential norms from 1996-97 onwards, have helped to generate an awareness for adverse effects of overdues/ non - performing assets in these banks. But the percentage of overdues to total loans has still been a matter of concern for the Gurdaspur Central Cooperative Bank, the Ferozepur Central Cooperative Bank and the Fazilka Central Cooperative Bank.